NEUROLINGUISTIC SPEECH DISORDERS: APHASIA, APRAXIA, AND AGNOSIA - Mirzayeva , Go‘zal (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
Background: Neurolinguistic speech disorders, including aphasia, apraxia, and agnosia, significantly impact communication by disrupting different aspects of language and cognitive processing. Specific Background: Aphasia results from brain damage affecting language processing, apraxia impairs the motor planning required for speech production, and agnosia involves the inability to recognize familiar objects or sounds despite preserved sensory functions. Knowledge Gap: Despite substantial research into these disorders, there remains a need for comprehensive analysis and integration of their phonetic and phonological dimensions, as well as the development of targeted rehabilitation strategies to address these aspects effectively. Aims: This study aims to analyze the phonetic and phonological aspects of aphasia, apraxia, and agnosia and to propose rehabilitation strategies that focus on phonological and phonetic retraining to improve communication abilities in affected individuals. Results: The analysis reveals distinct phonetic and phonological challenges associated with each disorder. Aphasia is characterized by deficits in language processing, apraxia by disruptions in speech motor planning, and agnosia by impaired recognition of sounds and objects. Rehabilitation strategies that emphasize phonological and phonetic retraining have shown promise in enhancing recovery and improving communication abilities. Novelty: This research integrates findings from leading experts to provide a comprehensive overview of how these disorders affect phonetic and phonological processes and highlights novel rehabilitation approaches tailored to address these specific challenges. Implications: The study underscores the importance of targeted rehabilitation strategies in improving communication outcomes for individuals with neurolinguistic speech disorders and suggests further investigation into the effectiveness of these interventions in clinical settings.